Circulating microparticles, protein C, free protein S and endothelial vascular markers in children with sickle cell anaemia. Issue 1 (23rd November 2015) - Piccin, Andrea; Murphy, Ciaran; Eakins, Elva; Kunde, Jan; Corvetta, Daisy; Di Pierro, Angela; Negri, Giovanni; Guido, Mazzoleni; Sainati, Laura; Mc Mahon, Corrina; Smith, Owen Patrick; Murphy, William
Abstract : Introduction: Circulating microparticles (MP) have been described in sickle cell anaemia (SCA); however, their interaction with endothelial markers remains unclear. We investigated the relationship between MP, protein C (PC), free protein S (PS), nitric oxide (NO), endothelin‐1 (ET‐1) and adrenomedullin (ADM) in a large cohort of paediatric patients. Method: A total of 111 children of African ethnicity with SCA: 51 in steady state; 15 in crises; 30 on hydroxyurea (HU) therapy; 15 on transfusion; 17 controls (HbAA) of similar age/ethnicity. MP were analysed by flow cytometry using: Annexin V (AV), CD61, CD42a, CD62P, CD235a, CD14, CD142 (tissue factor), CD201 (endothelial PC receptor), CD62E, CD36 (TSP‐1), CD47 (TSP‐1 receptor), CD31 (PECAM), CD144 (VE‐cadherin). Protein C, free PS, NO, pro‐ADM and C‐terminal ET‐1 were also measured. Results: Total MP AV was lower in crisis (1.26×10 6 ml −1 ; 0.56–2.44×10 6 ) and steady state (1.35×10 6 ml −1 ; 0.71–3.0×10 6 ) compared to transfusion (4.33×10 6 ml −1 ; 1.6–9.2×10 6, p<0.01). Protein C levels were significantly lower in crisis (median 0.52 IU ml −1 ; interquartile range 0.43–0.62) compared with all other groups: HbAA (0.72 IU ml −1 ; 0.66–0.82, p<0.001); HU (0.67 IU ml −1 ; 0.58–0.77, p<0.001); steady state (0.63 IU ml −1 ; 0.54–0.70, p<0.05) and transfusion (0.60 IU ml −1 ; 0.54–0.70, p<0.05). In addition, levels were significantly reduced in steady state (0.63 IU ml −1 ; 0.54–0.70) compared with HbAA (0.72 IU ml −1 ; 0.66–0.80, p<0.01). PS levels were significantly higher in HbAA (0.85 IU ml −1 ; 0.72–0.97) compared with crisis (0.49 IU ml −1 ; 0.42–0.64, p<0.001), HU (0.65 IU ml −1 ; 0.56–0.74, p<0.01) and transfusion (0.59 IU ml −1 ; 0.47–0.71, p<0.01). There was also a significant difference in crisis patients compared with steady state (0.49 IU ml −1 ; 0.42–0.64 vs. 0.68 IU ml −1 ; 0.58–0.79, p<0.05). There was high correlation (R>0.9, p<0.05) between total numbers of AV‐positive MP (MP AV) and platelet MP expressing non‐activation platelet markers. There was a lower correlation between MP AV and MP CD62P (R=0.73, p<0.05) (platelet activation marker), and also a lower correlation between percentage of MP expressing CD201 (%MP CD201) and %MP CD14 (R=0.627, p<0.001). %MP CD201 was higher in crisis (11.6%) compared with HbAA (3.2%, p<0.05); %MP CD144 was higher in crisis (7.6%) compared with transfusion (2.1%, p<0.05); %CD14 (0.77%) was higher in crisis compared with transfusion (0.0%, p<0.05) and steady state (0.0%, p<0.01); MP CD14 was detectable in a higher number of samples (92%) in crisis compared with the rest (40%); %MP CD235a was higher in crisis (17.9%) compared with transfusion (8.9%), HU (8.7%) and steady state (9.9%, p<0.05); %CD62E did not differ significantly across the groups and CD142 was undetectable. Pro‐ADM levels were raised in chest crisis: 0.38 nmol L −1 (0.31–0.49) versus steady state: 0.27 nmol L −1 (0.25–0.32; p<0.01) and control: 0.28 nmol L −1 (0.27–0.31; p<0.01). CT‐proET‐1 levels were reduced in patients on HU therapy: 43.6 pmol L −1 (12.6–49.6) versus control: 55.1 pmol L −1 (45.2–63.9; p<0.05). NO levels were significantly lower in chest crisis (19.3 mmol L −1 plasma; 10.7–19.9) compared with HU (22.2 mmol L −1 plasma; 18.3–28.4; p<0.05), and HbSC (30.6 mmol L −1 plasma; 20.8–39.5; p<0.05) and approach significance when compared with steady state (22.5mmol L −1 plasma; 16.9–28.2; p=0.07). Conclusion: Protein C and free PS are reduced in crisis with lower numbers of platelet MP and higher percentage of markers of endothelial damage and of red cell origin. During chest crisis, ADM and ET‐1 were elevated suggesting a role for therapy inhibiting ET‐1 in chest crisis.